1967
DOI: 10.1111/j.1365-2141.1967.tb08844.x
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Survival and Splenic Accumulation of Radiochromium in Liver Cirrhosis with Splenomegaly

Abstract: SUMMARY Red cell survival was studied in 22 cirrhotic patients and in four healthy volunteers by the 51Cr method. Seven patients (32 per cent) showed a definite reduction in the apparent half survival time (51Cr T4 below 20 days). Eight patients (36 per cent) showed a borderline reduction (51Cr T4 20–24 days). Seven patients (32 per cent) showed a normal 51Cr T4 of 25 days or more. All four controls had 51Cr T4 of 25 days or more. Surface counting over the spleen showed excess spleen counts more marked in thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…The authors also found that the percentage of patients with low folate levels (Ͻ4.1 ng/mL) was significantly higher in patients with alcoholic liver cirrhosis versus patients with non-alcoholic liver cirrhosis (35% vs. 9%), whereas actual folate deficiency (Ͻ2.5 ng/mL) was only observed among patients with alcoholic liver cirrhosis (17% of patients). Other causes of anemia in cirrhotic patients include reduced survival of red blood cells (13); hemolysis secondary to an enlarged spleen, which sequesters and destroys blood cells and leads to macro-normoblastic bone marrow (14); and renal insufficiency (15). Patt et al (16) reported that independent predictors of anemia (Hb Ͻ12 g/dL) in patients awaiting liver transplantation include serum creatinine (Ͼ12 mg/L), prothrombin time, and bilirubin and albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that the percentage of patients with low folate levels (Ͻ4.1 ng/mL) was significantly higher in patients with alcoholic liver cirrhosis versus patients with non-alcoholic liver cirrhosis (35% vs. 9%), whereas actual folate deficiency (Ͻ2.5 ng/mL) was only observed among patients with alcoholic liver cirrhosis (17% of patients). Other causes of anemia in cirrhotic patients include reduced survival of red blood cells (13); hemolysis secondary to an enlarged spleen, which sequesters and destroys blood cells and leads to macro-normoblastic bone marrow (14); and renal insufficiency (15). Patt et al (16) reported that independent predictors of anemia (Hb Ͻ12 g/dL) in patients awaiting liver transplantation include serum creatinine (Ͼ12 mg/L), prothrombin time, and bilirubin and albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…3 Currently, several measurements such as glycated haemoglobin (HbA 1C ), glycated albumin (GA), fructosamine and 1,5-anhydroglucitol (1,5-AG) are used as clinical markers for glycaemic control. However, it is demonstrated that CLD patients have apparently low HbA 1C 4 -6 due to shortened lifespan of erythrocytes, 7 which is caused by hypersplenism. Furthermore, since ability of albumin synthesis is impaired and half-life of serum albumin is prolonged in CLD patients, their serum GA levels appear to be high relative to glycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, GA levels in patients with such diseases do not properly indicate the status of glycaemic control. 8 In chronic liver disease (CLD), hypersplenism reduces the life span of erythrocytes 9 and thus HbA 1C levels are set relatively low in relation to plasma glucose levels.…”
Section: Introductionmentioning
confidence: 99%